How Popular Music is Exhibited by Museums in Portugal at the Beginning of the Twenty‐First Century: A Case Study. (April 2016) - Cortez, Alcina
Abstract: Popular music is deeply embedded in the dynamics of the contemporary world by means of its capacity to engender modes of privacy and publicness, to communicate emotion, and to enable us to create connections—and so to work within communities. Museums have traditionally addressed art‐music through the exhibition of musical instruments. But now that the exhibition of popular music has presented new challenges and opportunities worldwide for museum professionals, examining popular music discourses in museums is of the utmost importance in order for it to be meaningfully celebrated as instances of heritage. This paper expands on the representation of Popular Music in museums in Portugal at the beginning of the twenty‐first century by discussing a case study: the exhibition No Tempo do Gira‐Discos: Um Percurso Pela Produção Fonográfica Portuguesa at Museu Nacional da Música, Lisbon, Portugal, in 2007. Two methods of analysis are deployed: interviews with the curators, which revealed insights on their understanding of popular music, and analysis of the exhibition through discourse analysis, specifically through the lens of the analytical concepts genre and register . Although the curators had themselves previously developed insightful and innovative concepts with regard to popular music, discourse analysis reveals how, in this instance, the museum practices were primarily inherited from past traditions, and so failed to convey the meanings previously envisioned by the curators. In order for genuine public engagement with museum exhibitions about music, a collaboration is required between the music studies and museum studies professionals. Only through such a collaboration can it be ensured that those contemporary dynamics are present and meaningful.